Biochemical Studies During Different Pathological Conditions In Kidneys Of Buffaloes - Singh, Shailendra; Garg , U.K.; Shukla , Supriya (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present investigation was carried out to study the spontaneous occurrence of various pathological conditions and their pathomorphological alterations in the kidneys of buffaloes, with possible correlation to biochemical parameters. Blood urea nitrogen was significantly higher in all pathological conditions of kidneys. Serum total proteins were higher in case of renal infarction, fatty degeneration, pyelonephritis, polycystic kidney, calcification, embolic nephritis and pigmentation. Total protein was found to be lower in case of amyloidosis, interstitial nephritis, hydronephroosis, and nephrolithiasis.
Keywords: Biochemical; Serum total protein; Blood Urea Nitrogen; Serum glucose; kidney